APPRAISAL SYSTEM ON THE JAKARTA POST OPINION “A HUMAN RIGHTS MEMORIAL: JOKOWI AND THE SORCERER’S STONE” - Pikir Wisnu Wijayanto (Universitas Islam Negeri Walisongo Semarang, 2016)
This study aims at examining the meaning of text in detail through metafunctions analysis with appraisal systems. The appraisal system is deployed in order to explore texts in detail from the perspectives of discourse semantics developed by James Martin and David Rose (2003). The data is taken from the opinion article column of the Jakarta Post (a national English newspaper in Indonesia), published on Thursday, October 23rd, 2014. The article entitled “A Human Rights Memorial: Jokowi and the Sorcerer’s Stone” written by Barikatul Hikmah. According to the appraisal systems of attitude text, the writer uses more positive option for affect the reader than the negative options. The dominant positive options are used in order to express the writer’s opinions, suggestions, and expectation to the Jokowi’s government, in term of Jokowi’s commitment to human rights enforcement and the importance of building a human rights memorial. The direct opinion for affect in emotional states category used around 13 expressions, and 4 words and phrases for showing the physical expressions. The implicit opinion of clause used in this article consist of 2 extraordinary behavior expressions and 3 metaphors expressions. In the amplifying of (gradable) attitudes text, the article is expressing the force of attitudes (intensifiers) that make it possible for us to compare things or to say how strongly we feel about someone or something by making comparison to others. Related to the source of attitude analysis, the text is a narrative with some clauses containing the affect values. The writer can be said to be fully responsible for all of the evaluation, and the sources of attitudes are attributable to the writer’s expectation.